2021
DOI: 10.1109/ojpel.2021.3069780
|View full text |Cite
|
Sign up to set email alerts
|

A Partial Discharge Study of Medium-Voltage Motor Winding Insulation Under Two-Level Voltage Pulses With High Dv/Dt

Abstract: Medium-voltage (e.g. 10 kV rated) silicon carbide (SiC) devices have great potentials in medium-voltage variable speed drives. But their high switching dv/dt can increase the voltage stress on motor windings and cause partial discharges. This paper presents a partial discharge study of a medium-voltage form-wound winding under two-level square-wave voltage pulses. A 10 kV SiC device-based test platform is built to generate voltage pulses with high dv/dt. A three-step test approach is proposed and employed to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Moreover, because PD activities depend on the peak-topeak value of excitation voltage, the PDIV of the unipolar waveform should be at least double that of the bipolar waveform. The experimental results in [35] are consistent with this finding. Compared with unipolar waveform, bipolar waveform excitation is the worst case for PD detection, and this also corresponds to the instruction mentioned in standard IEC/TS 61934:2011 [58].…”
Section: Electrical Filed Change Of Air Gap Under Bipolar Waveform Ex...supporting
confidence: 88%
See 2 more Smart Citations
“…Moreover, because PD activities depend on the peak-topeak value of excitation voltage, the PDIV of the unipolar waveform should be at least double that of the bipolar waveform. The experimental results in [35] are consistent with this finding. Compared with unipolar waveform, bipolar waveform excitation is the worst case for PD detection, and this also corresponds to the instruction mentioned in standard IEC/TS 61934:2011 [58].…”
Section: Electrical Filed Change Of Air Gap Under Bipolar Waveform Ex...supporting
confidence: 88%
“…It can be concluded that regardless of the test objects or insulation models, both the PDIV and PDEV for shorter rise time PWM waveform (unipolar and bipolar) are lower than those of longer rise time waveform, and the PDIV & PDEV values for DC excitation are always larger than both unipolar and bipolar PWM waveform. [35] tests the RPDIV of Type II machine insulation. It finds when the peak-to-peak value is fixed (ignoring overshoot), the RPDIV of motor insulation is slightly higher under bipolar voltage excitation.…”
Section: ) Rise Timementioning
confidence: 99%
See 1 more Smart Citation
“…Many approaches have been proposed to investigate the effects of various parameters of repetitive impulse voltage stress, including voltage duty cycle, voltage frequency, voltage rise/fall time, voltage amplitude, and voltage polarity. Hu et al [33] investigated the effects of various voltage parameters on partial discharges of medium-voltage form-wound winding. They obtained an empirical equation to estimate partial discharge inception voltages (PDIV) at various voltage rise/fall times and pulse width conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al. [33] investigated the effects of various voltage parameters on partial discharges of medium‐voltage form‐wound winding. They obtained an empirical equation to estimate partial discharge inception voltages (PDIV) at various voltage rise/fall times and pulse width conditions.…”
Section: Introductionmentioning
confidence: 99%